2020
DOI: 10.1186/s12936-020-03266-w
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of human exposure to malaria vectors in Zanzibar and implications for malaria elimination efforts

Abstract: Background: Zanzibar provides a good case study for malaria elimination. The islands have experienced a dramatic reduction in malaria burden since the introduction of effective vector control interventions and case management. Malaria prevalence has now been maintained below 1% for the past decade and the islands can feasibly aim for elimination. Methods: To better understand factors that may contribute to remaining low-level malaria transmission in Zanzibar, layered human behavioural and entomological researc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
(44 reference statements)
0
21
1
Order By: Relevance
“…where and when residual transmission is expected to occur. Numerous studies have used this model in Africa [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. However until now, only one of these studies has reported exposure estimates for sites located in Burkina Faso [18].…”
Section: Introductionmentioning
confidence: 99%
“…where and when residual transmission is expected to occur. Numerous studies have used this model in Africa [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. However until now, only one of these studies has reported exposure estimates for sites located in Burkina Faso [18].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the distributions of bites between inside and outsides the houses and at different times of the night [1,2], what mosquitoes feed upon critically determines the choice and impact of human-targeted vector control interventions [3][4][5][6][7][8]. For example, both historical and recent reports [9][10][11][12][13][14] show that the widespread use of long-lasting insecticide-treated nets (LLNs) or indoor residual spraying (IRS), which directly target humans or houses they live in, strongly suppressed or virtually eliminated the population of the main malaria vectors Anopheles gambiae sensu stricto, and Anopheles funestus sensu stricto.…”
Section: Introductionmentioning
confidence: 99%
“…If a false classification was made, a record was made of the correct class. The classification points were used to construct an error matrix for each site, which was subsequently used to calculate accuracy statistics, including % overall accuracy, kappa coefficient and quantity and allocation disagreement scores [30].…”
Section: Accuracy Assessmentmentioning
confidence: 99%